Device Strategies for Patients in INTERMACS Profiles 1 and 2 Cardiogenic Shock: Double Bridge With Extracorporeal Membrane Oxygenation and Initial Implant of More Durable Devices. Issue 3 (23rd September 2016) - Cheng, Richard; Ramzy, Danny; Azarbal, Babak; Arabia, Francisco A.; Esmailian, Fardad; Czer, Lawrence S.; Kobashigawa, Jon A.; Moriguchi, Jaime D.
Abstract: For Interagency Registry for Mechanically Assisted Circulatory Support profiles 1 and 2 cardiogenic shock patients initially placed on extracorporeal membrane oxygenation (ECMO), whether crossover to more durable devices is associated with increased survival, and its optimal timing, are not established. Profiles 1 and 2 patients placed on mechanical support were prospectively registered. Survival and successful hospital discharge were compared between patients placed on ECMO only, ECMO with early crossover, and ECMO with delayed crossover. Survival of patients directly implanted with non‐ECMO devices was also reported. One‐hundred and sixty‐two patients were included. Mean age was 52.2 ± 13.8 years. Seventy‐three of 162 (45.1%) were initiated on ECMO. Of these, 43 were supported with ECMO only, 11 were crossed‐over early <4 days, and 19 were crossed‐over in a delayed fashion. Survival was different across groups (Log‐rank P  < 0.002). In multivariate analysis, early crossover was associated with decreased mortality as compared with no crossover (hazard ratio [HR] 0.201, 95% confidence interval [95%CI] 0.058–0.697, P  = 0.011) or with delayed crossover (HR 0.255, 95%CI 0.073–0.894, P  = 0.033). Mortality was not different between delayed crossover and no crossover ( P  = 0.473). In patients with early crossover there were no deaths at 30 days, and 60‐day survival was 90.0 ± 9.5%. Survival to hospital discharge was 72.8%. For patients directly implanted with non‐ECMO devices, 30‐day and 60‐day survival was 90.9 ± 3.1% and 87.3 ± 3.8%, respectively, and survival to hospital discharge was 78.7%. Both initial implant of durable devices and double bridge strategy was associated with improved outcomes. If the double bridge strategy is chosen, early crossover is associated with improved survival and successful hospital discharge.